Students' Mathematical Problem-Solving Ability in Bengkulu Tabot Context Based on Polya Steps - Hanny Nurhikma Prapti; Susanto, Edi; Hari Sumardi (EDUPEDIA Publisher, 2023)
This study aims to analyze the ability to solve mathematical problems in the context of Tabot in Bengkulu state junior high school based on Polya's steps. This type of research is descriptive research with a qualitative approach. Methods of data collection in the form of a test about the ability to solve mathematical problems in the context of Tabot, interviews, and competencies. The results of this study found that the average of all mathematical problem-solving abilities of state junior high school students was 46.54% with sufficient criteria. The average student in the ability to understand the problem is 54.08% with sufficient comparison, the average in the ability to compose problems is 50.45% with sufficient withdrawal, the average problem solving is 43.53% with sufficient comparison, and the average at the conclusion is 34.15% with low criteria. It is suggested to teachers practice solving problem-solving questions.